Pengaruh Model Discovery Learning dengan Pendekatan Contextual Teaching Learning terhadap Keterampilan Argumentasi Tertulis Siswa ditinjau dari Kemampuan Akademik - Anugraheni, Annisa Dhimar; Oetomo, Dwi; Santosa, Slamet (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2018)
The purpose of this research is to determine the effect of discovery learning model with contextual teaching learning (ctl) approach to written skill argumentation students of karangpandan senior high school.. The research was considered as quasi experiment research using Pretest-Posttest Non-equivalent Control Group design. Sampling technique using cluster sampling. The study population is all students of class XI MIA SMA N Karangpandan Academic Year 2017/2019 consisting of six classes. Sample of class consists oftwo classes, eksperiment class with discovery learning model with contextual teaching learning (ctl) approach and control class with discovery learning. Data collection techniques use essays test, observations, and documentation. The normality test with Kolmogorov-Smirnov test and homogeneity with Levene test. Hypothesis test used is Paired Sample t test with 5% (α= 0.05) significance level assisted with SPSS 21. The research procedure includes planning, implementation and data analysis. The conclusion of this research show that the application of discovery learning model with contextual teaching learning (ctl) approach has given effect towards student’s argumentation skill